Copper-Catalyzed Regiospecific and 1,2-Regioselective Cyclopropanation of (1Z)-1-Amino- and (1Z)-1-Oxy-1,3-butadienyl Derivatives - Tayama, Eiji; Saito, Shun (Synlett, 2015)
The copper-catalyzed regiospecific and 1,2-regioselective cyclopropanation of (1Z)-1-amino- and (1Z)-1-oxy-1,3-butadienyl derivatives, which could be prepared by Z-stereoselective 1,4-elimination with α-aryl diazoesters was successfully demonstrated. This successful regiospecific protocol enabled the preparation of the corresponding 1-amino- and 1-oxy-2-vinylcyclopropane derivatives as almost single stereoisomers.
Keywords: cycloaddition; diastereoselectivity; diazo compounds; regioselectivity; stereoselective synthesis